IMPLEMENTASI PERATURAN DAERAH NOMOR 27 TAHUN 2011 TENTANG PENGELOLAAN RETRIBUSI PELAYANAN SAMPAH DI DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PALEMBANG PADA KASUS PASAL 32 - A.Ridhuan Habena (Social and Political Sciences Faculty, Widya Gama Mahakam Samarinda University, 2025)
Implementation of Palembang City Regional Regulation Number 27 of 2011 Concerning Waste Management and Service Retribution at the Palembang City Environmental and Sanitation Service (Case Study of Article 32 Principles and Targets of Determining Household Waste Retribution Tariffs Sukabangun Indah Phase II Sukajaya Village). The background of this study is Based on temporary findings at the Palembang City Environmental and Sanitation Service regarding the principles and targets of determining household waste retribution tariffs, a case study of Sukajaya Village Sukabangun Indah Phase II, the problems faced are not paying attention to the cost of providing services, tariffs are not in accordance with government regulations so that they vary from Rp. 30,000 to Rp. 50,000 for waste contributions, unfairness in service, ineffectiveness of service provision in terms of waste transportation past the specified due date. The method used in this study is a qualitative method that directly presents the nature of the relationship between researchers and informants, objects and subjects of research. The theory used is Edward III in (2004:168) and (Palembang City Regional Regulation Number 27 of 2011 Concerning Waste Management and Service Retribution) is to process and analyze the collected data into systematic, orderly, structured and meaningful data for research showing the Importance of Principles and Targets for Determining Household Waste Retribution Tariffs for Sukabangun Indah Phase II, Sukajaya Village.